Primary extragastrointestinal stromal tumors of the prostate: A case report and literature review - Yang, Yuxuan; Sun, Dengshun; Tang, Kun (Frontiers in Oncology, 2022)
Gastrointestinal stromal tumors（GISTs） are the main stromal tumors of the digestive tract. Extra-gastrointestinal stromal tumors（EGISTs） typically originate outside the gastrointestinal tract, are not associated with the stomach wall or intestinal wall, and are mainly derived from the mesentery, peritoneum, posterior peritoneum, bladder, and scrotum. However, extra-gastrointestinal stromal tumors from the prostate are rare. Right here, we file a case of EGIST that passed off in the prostate of a 62-year-old man. The patient undergoes transrectal guided trans-perineal prostate puncture, and pathological reports suggest a gastrointestinal stromal tumor. Tumor cells are spindle-shaped, and no obvious neoplastic necrosis is seen in the sections. Immunohistochemical results were robust positive for CD117, DOG-1, and CD34 expression. The patient had a good prognosis after treatment with imatinib, no recurrence and no metastases after six months of follow-up, and the prognosis was good. This article also provides a literature review and discussion of the treatment of EGISTs.